PENGEMBANGAN INSTRUMEN TES HIGHER ORDER THINKING SKILLS (HOTS) UNTUK MENGUKUR KEMAMPUAN BERPIKIR SISWA PADA MATERI SISTEM PERNAPASAN MANUSIA - Nur Saadah Sihombing Sihombing; Almira Amir; Misahradarsi Dongoran (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
The background of this research is the question of the daily test of Class XI IPA on the material of human respiratory system at MAN Sibolga Plus Skills then the question was analyzed by the researcher. The results of the question analysis indicated that MAN Sibolga Plus Skills students still used tests that tended to be categorized as Low Order Thinking Skills (LOTS), so the researchers raised the issue of developing Higher Order Thinking Skills (HOTS) instruments to measure students' thinking skills. The research and development (RD) method used in this study by applying the 4D development model (Define, Design, Develop, and Disseminate). The instruments used in this study were validation and questionnaire. The results of this study were experts validated the questionnaire and instrument to the validator then the validator provided comments and assessments, namely that the Higher Order Thinking Skills (HOTS) test instrument product to measure students' thinking skills on the material of the respiratory system has a very high level of validity with an average of 87.25%. The results of data analysis from the practicality questionnaire from the teacher response at State Senior High School (SMAN) 1 Pinangsori reached a percentage of 100% and the results of the student response questionnaire with a sample of 36 students reached an average value of 93.8% with a very practical category. The Higher Order Thinking Skills (HOTS) test instrument used to measure students' thinking skills on this respiratory material is included in the highly effective category. The effectiveness of this Higher Order Thinking Skills (HOTS) test instrument can be seen with an average value of 83.86%, with a very high category.